Pengaruh Rasio Keuangan Terhadap Harga Saham - Permatasari, Sheila Silvia; Mukaram, Mukaram (Jurnal Riset Bisnis dan Investasi, 2018)
This study aims to influence the financial ratios of stock prices on the issuers of automotive sector companies and components listed on the Indonesia Stock Exchange period 2011-2016. This study is a documentation study, where the data used is secondary data obtained from company reports that have been available. The population in this research is all companies of automotive sector and components listed in IDX and reporting company's finance in period 2011-2016. From a total of 13 companies, 12 companies were taken as samples because one company did not meet the requirements of the financial statements for the period in this study. Data analysis was done by multiple linear regression analysis and hypothesis test by using t test and F test. The result showed that DERand PER have negative and significant effect to stock price in automotive company and component listed on IDX 2011-2016, TATO has a positive and insignificant effect on stock prices in automotive companies and components listed on IDX 2011-2016, CR and ROA have negative and significant effect on stock price in automotive company and component listed on IDX 2011-2016.